Synthesis of microwave bandpass filters based on planar quarter-wavelength resonators - Zhang, Songbai (2014)
This Ph.D thesis is dedicated to explicitly synthesize the size-miniaturized and robustly-performed microwave bandpass filters based on planar quarter-wavelength (λ/4) resonators. Unlike the conventional bandpass filters (BPFs) based on J coupling only or K coupling only, λ/4 resonators are necessarily coupled by alternative J and K inverters to realize BPFs. The exemplified filters in this thesis not only include single-band bandpass filters (SB-BPFs) with all-pole Chebyshev and quadruplet frequency responses, but also the dual-band bandpass filters (DB-BPFs) and a tri-band bandpass filter (TB-BPF) based on the λ/4 stepped impedance resonators (SIRs).